Making food systems work for complementary feeding in low- and middle-income countries: Meeting Report - Micronutrient Forum (Micronutrient Forum, 2024)
Food systems currently are not meeting the needs of children in low- and middle-income countries (LMICs). across the globe. In these countries, two in three children between the ages of 6 and 23 months lack the diverse diets they need for healthy growth, development, and future economic success. Nutrient requirements of children in this age group are high due to rapid growth and development while the quantities of food they can consume to meet these requirements is small, highlighting the need for locally grown nutrient-dense foods and in contexts where these are not available, fortified complementary foods. Low availability and unaffordability of diverse foods appropriate for young children limit access to a nutritious diet. Bold actions are needed to ensure that food systems and more particularly, agricultural production, food supply chains, and food environments sustainably provide healthier and more nutritious diets for this vulnerable age group. On behalf of the United States Agency for International Development (USAID), the Micronutrient Forum (the “Forum”) and USAID Advancing Nutrition organized an expert consultation on December 4–5, 2023 on food system approaches to discuss strategies to increase the availability, affordability, accessibility, and aspirational aspects of nutritious and safe foods appropriate for complementary feeding that can be purchased by low-income households. The 43 participants’ expertise covered nutrition, food systems from local to global levels, policy and business expertise and represented research, bilateral, technical, and implementing organizations, United Nations agencies, and the private sector.